INFLUENCE OF RISK TOLERANCE TO DECISION MAKING EFFECTIVENESS, A CASE STUDY FROM PERTAMINA SUB HOLDING UPSTREAM - Muslim, Aziz
This research investigates the influence of risk tolerance, decision style on decisionmaking effectiveness in the context of PERTAMINA Sub Holding Upstream. The study utilizes statistical methods including Structural Equation Modelling, Confirmatory Factor Analysis, and bootstrapping to assess the significant influence of risk tolerance on decision effectiveness.